Review of the genus Anacranae Miller, 1934 (Orthoptera: Acrididae: Catantopinae) - Dawwrueng, Pattarawich; Storozhenko, Sergey Yu.; Suwannapoom, Chatmongkon (Zootaxa, 2025)
The genus Anacranae Miller includes five species distributed in Thailand, Malaysia and Vietnam. A new species, Anacranae maculata sp. nov., is described from northern Thailand. Hitherto unknown male of Anacranae vietnamensis Storozhenko is described and this species is recorded from Thailand for the first time. Anacranae beybienkoi Storozhenko known from northeastern Thailand is also widely distributed in western and northern Thailand. Anacranae nuda Miller and A. gorochovi Storozhenko are endemic to peninsular Malaysia and South Vietnam respectively. A key to species of Anacranae is also given.